2005
DOI: 10.1093/humrep/deh601
|View full text |Cite
|
Sign up to set email alerts
|

Dose-finding study of daily GnRH antagonist for the prevention of premature LH surges in IVF/ICSI patients: optimal changes in LH and progesterone for clinical pregnancy

Abstract: Excessive or insufficient suppression of LH and progesterone levels during GnRH antagonist administration and high progesterone/follicle on hCG day seems to be associated with impaired clinical pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 37 publications
5
50
2
1
Order By: Relevance
“…This demonstrated that E 2 pre-treatment before GnRH-antagonist protocol, especially before the GnRH antagonist injection, had increased incidence rate of premature LH, which is similar to the previous report by Durnerin IC et al [11]. This could be clinically relevant because pregnancy rate seems optimal within a certain window of LH secretion in GnRH antagonist cycles [15]. Kolibianakis et al [16] suggested that the lower the LH levels, the higher probability of pregnancy in GnRH antagonist protocol.…”
Section: Discussionsupporting
confidence: 80%
“…This demonstrated that E 2 pre-treatment before GnRH-antagonist protocol, especially before the GnRH antagonist injection, had increased incidence rate of premature LH, which is similar to the previous report by Durnerin IC et al [11]. This could be clinically relevant because pregnancy rate seems optimal within a certain window of LH secretion in GnRH antagonist cycles [15]. Kolibianakis et al [16] suggested that the lower the LH levels, the higher probability of pregnancy in GnRH antagonist protocol.…”
Section: Discussionsupporting
confidence: 80%
“…We also did not find relationship between serum LH levels and miscarriages among all patients and among pregnant women. Even though other studies reveal lack of association between IVF outcome and the LH level on the beginning [49,50] and during [51][52][53][54] COH, they did not concern PCOS patients. Study by Lainas et al [55] described significantly lower LH levels on days 3 and 5 and significantly higher LH levels on days 1, 7 and 8 of stimulation in the antagonist when compared with the agonist group among PCOS women.…”
Section: Discussionmentioning
confidence: 91%
“…However, mid-to late-follicular phase LH serum levels in GnRH antagonist treated patients did not influence follicular maturation, pregnancy rates or outcomes (22), or were even inversely correlated with ongoing pregnancy rate (23). In two prospective studies it was demonstrated, that in GnRH antagonist protocols excessive or insufficient suppression of LH levels was associated with impaired clinical pregnancy rates (24), whereas in an unselected group of patients there was no beneficial evidence for recombinant LH supplementation (25).…”
Section: Discussionmentioning
confidence: 95%